Note: Determine whether the solution to the new equation is a solution to the old system of equations by graphing. Use Desmos!

The solution to the original system of equations
Solve the system of equations by SUBSTITUTION. (is also, is not)

6y + 5x = 8

x + 3y = - 7

What would your equation look like after the first substitution? (6y + 5(3y - 7) = 8, 6y + 5(- 3y - 7) = 8, 6(- 3y - 7) + 5x = 8, 6(3y + 8) + 5x = - 7)

1 answer

The equation after the first substitution would be: 6y + 5(3y - 7) = 8.
Similar Questions
    1. answers icon 1 answer
  1. Question 1Examine the equation that follows: 4. 2y=6x+2 determine how this equation forms a system with one solution, no
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions